The geophysical signature of Oyut deposits, Oyu Tolgoi, Mongolia - Batbaatar, Erdene; Todbileg, Munkhjargal; Sansar, Otgonbayar; Bataa, Baatar (Mongolian Geoscientist, 2021)
The well-known Oyu Tolgoi Cu-Au group deposits can be divided into three main deposits: Hugo Dummett deposit (Hugo North and Hugo South), Oyut deposits (South Oyu, Southwest Oyu and Central Oyu), and Heruga deposit in the south. These deposits sit along 26 km long, north-northeast trending belt termed as the Oyu Tolgoi trend. This paper reviews investigations on geophysical signatures of the South Oyu, Southwest Oyu and Central Oyu deposits and compares geophysical models of the mineral deposits with their lithology, alteration, mineralization, and structures. A variety of datasets including induced polarization, ground magnetic, gravity survey are used in the study and generated inversion products of ground magnetic and gravity data with integrated interpretation. Typical responses from the Oyut deposits are: up to 0.1 mGal positive gravity anomaly above background, 100–200 nT low or high magnetic anomaly compared to background depending on the geological situations, and from 12 mV/V to 30 mV/V chargeability anomalies and low resistivity signatures from 100 ohm.m to 400 ohm.m. The interpreted geological-geophysical models of porphyry Cu-Au deposits presents in this study have emphasis on integrated interpretation of geophysical techniques, and inversions of gravity and magnetic data in gold rich porphyry copper system.